Effects of Whole-Body Vibration on Ankle Control and Walking Speed in Individuals with Incomplete Spinal Cord Injury - Jasmine M. Hope; Anastasia Zarkou; Cazmon Suri; Edelle C. Field-Fote (Brain Sciences)
Background/Objectives: After spinal cord injury (SCI), poor dorsiflexor control and involuntary plantar-flexor contraction impair walking. As whole-body vibration (WBV) improves voluntary muscle activation and modulates reflex excitability, it may improve ankle control. In this study, the dosage effects of WBV on walking speed, dorsiflexion, and spinal reflex excitability were examined. Methods: Sixteen people with chronic motor-incomplete SCI participated in this randomized sham-control wash-in study. Two weeks of sham stimulation (wash-in phase) were followed by either 2 weeks of eight repetitions (short bout) or sixteen repetitions of WBV (long bout; intervention phase) per session. Walking speed, ankle angle at mid-swing, and low-frequency depression of the soleus H-reflex were measured before and after the wash-in phase and before and after the intervention phase. Results: A significant dosage effect of WBV was not observed on any of the measures of interest. There were no between-phase or within-phase differences in ankle angle during the swing phase or in low-frequency depression. When dosage groups were pooled together, there was a significant change in walking speed during the intervention phase (mean = 0.04 m/s, standard deviation = 0.06, p = 0.02). There was not a significant correlation between overall change in walking speed and dorsiflexion angle or low-frequency depression during the study. Conclusions: Whole-body vibration did not have a dosage-dependent effect on dorsiflexion during the swing phase or on spinal reflex excitability. Future studies assessing the role of corticospinal tract (CST) descending drive on increased dorsiflexor ability and walking speed are warranted.